2017
DOI: 10.3390/w9110875
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach Based on Numerical Modelling and Geophysical Survey to Map Groundwater Salinity in Fractured Coastal Aquifers

Abstract: Abstract:Aquifer over-exploitation may increase coastal seawater intrusion by reducing freshwater availability. Fractured subsurface formations commonly host important freshwater reservoirs along sea coasts. These water resources are particularly vulnerable to the contamination due to seawater infiltration occurring through rapid pathways via fractures. Modeling of density driven fluid flow in fractured aquifers is complex, as their hydrodynamics are controlled by interactions between preferential flow pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…For this reason, such measurements are increasingly combined with noninvasive geophysical techniques, able to image subsurface structures and rock-water interaction with high spatial resolution through physical parameters strictly related to the hydrological ones. In the last few decades, the use of electrical techniques to monitor infiltration dynamics became widespread due to the high sensitivity of the electrical resistivity to the water movement [19][20][21][22][23][24][25][26]. Particularly in the context of SAT and MAR applications, several study cases concerned time-lapse ERT monitoring [27][28][29][30][31][32] to investigate the sensitivity of the methods to changes in subsurface properties, to highlight the spatiotemporal distribution of the infiltrated water and improve the design and operation of MAR systems.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, such measurements are increasingly combined with noninvasive geophysical techniques, able to image subsurface structures and rock-water interaction with high spatial resolution through physical parameters strictly related to the hydrological ones. In the last few decades, the use of electrical techniques to monitor infiltration dynamics became widespread due to the high sensitivity of the electrical resistivity to the water movement [19][20][21][22][23][24][25][26]. Particularly in the context of SAT and MAR applications, several study cases concerned time-lapse ERT monitoring [27][28][29][30][31][32] to investigate the sensitivity of the methods to changes in subsurface properties, to highlight the spatiotemporal distribution of the infiltrated water and improve the design and operation of MAR systems.…”
Section: Introductionmentioning
confidence: 99%
“…Two papers in this special issue represented two examples of continuous endeavor for pushing the boundary of advanced numerical simulation techniques. In one of the two papers, Masciopinto et al [13] has proposed an innovative approach to model flow and salt transport in fractured coastal aquifers affected by seawater intrusion in Bari, Italy. The model was based on a stochastic method to transfer all real medium heterogeneities into the numerical model.…”
Section: Innovative Numerical Methodsmentioning
confidence: 99%
“…A more complex and data requiring approach is the one that make use of numerical models to deploy new characterization methods, for example, describing the linear and non-linear optimization approaches to manage seawater intrusion via numerical scenarios [144][145][146][147][148][149][150], or determining the long-term effects induced by pumping saline groundwater to feed desalination plants [151]. In addition, the employment of geophysical methods coupled with numerical models to quantify the aquifer salinization extension has been explored only in few studies [152][153][154][155], and only one reported the socio-economic aspects of SWI in the modeling procedure [156]. Finally, two studies have employed complex reactive transport models to quantify biogeochemical reactions induced by SWI [157][158][159].…”
Section: Data Handling Techniquesmentioning
confidence: 99%